Pendampingan Dan Penguatan Daycare Malnutrition Sebagai Upaya Penurunan Stunting Di Wilayah Kerja Puskesmas Sekaran - Mardiana; Salsa Billa; Syifa Salsa Bila; Shoofia Rihadhatul Aisy; Salma Eka Pratiwi; Safira Chairani Dimarti; Safrina Oksidriyani; Latifah Rachmawati; Elly Puji Kusumawati; Yovita Putri Anggraeni; Stevi Risqi Naola Sari; Maria Ulfa (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Malnutrition is a health problem that is still often found in developing countries. Based on SSGI data for 2022, the prevalence of stunting in Semarang City reached 10.4%. The Sekaran Community Health Center area recorded 3.07% of stunted toddlers in 2022, while as of December 2022 there were 74 underweight toddlers and 40 wasted toddlers. The establishment of daycare is one of the efforts made by the Sekaran Community Health Center to overcome the problem of stunting. This community service aims to assist nutritional care for toddlers with stunting at the Sekar Kasih Daycare located in Patemon Village, with the implementation of community service activities taking place since the daycare was established on March 1 2023 - August 1 2023. The programs offered and implemented include: other things include preparing a 10+1 day menu cycle, anthropometric measurements, GMP (Good Manufacturing Practices) training for 20 people consisting of daycare officers and posyandu cadres, preparing standard operating procedures (SOP) for organizing meals in daycares, and preparing a pocket book on food ingredient specifications. The results of this activity are a 10+1 day menu cycle, an increase in knowledge based on the average score from 89 to 96.5, and SOPs for managing food in daycare.